Karakteristik Bangunan â€œBale Piyasanâ€ Serta Proses Pembangunannya - Prayatna, Agus Eru; Widiyani, Desak Made Sukma (Jurnal Anala, 2020)
Bale Piyasan is one type of sacred building for the Hindu community, especially in Bali as an ancestral heritage that needs to be developed and preserved, so we need to know the background of the Bale Piyasan design and at the same time to know the historical and cultural values contained therein. At the same time as a comparison between the opinions of the sources and the reality in accordance with the conditions in the field, case studies which have different characteristics are carried out, both in terms of function, layout and shape of the sacred building. Based on this description, the purpose of this research is to find the meaning of the philosophy of the Bale Piyasan building, to find the process of self-reliance and physical, the rituals in constructing the Bale Piyasan and to determine the layout of the Bale Piyasan building as well. This research is a comparative descriptive study, where physical and non-physical data are collected, both library and field data. From the results of the analysis and comparison, they are reviewed and concluded to obtain a recommendation. There are 2 (two) types of data used in this study, namely primary data and secondary data. Primary data is obtained through (1) surveys and observations, namely making direct observations to objects and carrying out documentation, (2) interviews, which are conducted with people who are competent and can be trusted in this matter. Secondary data includes literature studies conducted to find information about research through information sources such as books, reports, the internet. From the results of literature and factual studies and analysis results, it can be concluded that Bale Piyasan is a rectangular elongated building with 4 (four) poles as a place to decorate or assemble symbols before being distributed to the sacred building and the place where the ceremony will be offered. Bale Piyasan functions as a place to decorate or arrange symbols, such as Daksina Pelinggih or Arca. The layout of Bale Piyasan is on the west side facing south. We can find Bale Piyasan in the innards of the temple. The Bale Piyasan design uses elbows or traditional Balinese measurements. The establishment of Bale Piyasan must follow the processes and ceremonies in accordance with the rules of traditional Balinese architecture.